A new species of the genus Pseudohampsonella Solovyev & Saldaitis (Lepidoptera: Limacodidae) from Xizang Autonomous Region, China - Wu, Jun; Zhao, Ting-Ting; Han, Hui-Lin (Zootaxa, 2022)
The sixth species of the genus Pseudohampsonella Solovyev & Saldaitis, 2014, P. medogensis sp. nov., is described from Xizang Autonomous Region, China. The new species is morphologically similar to the congeners P. bayizhena Wu & Pan, 2015 and P. hoenei Solovyev & Saldaitis, 2014, but differs from them by the uncus slightly waved with a blunt apex and the phallus distinctly curved mesally. Images of adults and genitalia are presented. The circumscription of the new species is supported molecularly by the analysis of the pairwise genetic distances using mitochondrial cytochrome c oxidase subunit I (COI) gene. The minimum interspecific distance value between the new species and its sister species, P. lii Wang & Li, 2017, is 7.7%.